Knowledge and attitudes toward anaphylaxis to local anesthetics in dental practice - Ivan Cherrez-Ojeda; Juan C. Gallardo-Bastidas; Gabriela Rouillon Borrero; Hans Mautong; Paola Andrea Mena Silva; Zouina Sarfraz; Azza Sarfraz; Leonardo Cano; Karla Robles-Velasco (Nature Publishing Group, 2024)
Abstract Objective/aim The absence of a comprehensive understanding of potential anaphylactic reactions to local anesthetics (LAs) and management can result in grave consequences. For this reason we aim to assess Latin American dentists' knowledge, preparedness, and competency in managing anaphylactic reactions to LAs. Materials and Methods Design: A cross-sectional study was conducted from November 2021 to February 2022. Board-certified dentists answered a survey comprising 26 structured questions. Chi-square tests and logistic regression models were performed in Stata 17.0. Setting: Argentina, Brazil, Colombia, Costa Rica, Ecuador, Honduras, Mexico, Peru, Venezuela, and other Latin American countries. Results Of 507 respondents, lidocaine was the most frequently used LA (88.1%). While 85.2% could identify dyspnea as a symptom of anaphylaxis, only 50.1% knew the correct route for epinephrine administration, and just 43.5% had epinephrine in their emergency kits. Confidence in managing anaphylactic reactions was low (9.6%). Older age was inversely related to both knowledge of anaphylaxis management and the possession of epinephrine (P = 0.003 and P = 0.0001, respectively). Discussion Our study highlights a concerning discrepancy between the practical readiness of Latin American dentists in handling anaphylaxis. Conclusion The study's findings underscore the need for educational interventions to improve the readiness to identify and handle anaphylactic emergencies in dental practice.